Parenting Patterns in Migrant Families And Their Effects on Early Childhood Socio-Emotional and Cognitive Development - Hosnol Hotimah; Rachma Hasibuan; Mallevi Agustin Ningrum; Kartika Rinakit Adhe; Denok Dwi Anggraini (Murhum : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to explore parenting patterns in Madurese migrant families and analyze their impact on early childhood socio-emotional and cognitive development. This study employs a qualitative approach with a case study design involving 5–8 Madurese migrant families with children aged 2–6 years. Data were collected through observation, in-depth interviews, and documentation, and analyzed using thematic analysis through data reduction, data display, and conclusion drawing, with validity ensured through triangulation. The findings indicate that parenting patterns in Madurese migrant families tend to be collective, involving extended family members such as grandparents or close relatives. This pattern provides positive impacts, including children’s social adaptability, empathy, and independence; however, it also presents challenges such as emotional longing, weakened parent–child attachment, difficulties in emotional regulation, and limited cognitive stimulation, which may lead to uneven academic development. Therefore, strengthening communication between parents and children, enhancing the capacity of substitute caregivers, and providing context-based policy support are necessary to minimize the negative impacts of migration on early childhood development.